Bodies, biopolitical critique, and female agency in contemporary bio(medical) artworks - Jankov, Sonja (Acta historiae artis Slovenica, 2025)
The paper investigates the societal and critical potential of bio(medical) artistic practices by focusing on the ways in which female artists use bodies and living cells as means of biopolitical critique. Using an ecofeminist and posthuman feminist theoretical framework, the author discusses selected bio(medical) works by female contemporary artists that contain living human cells or in which they connect with other species. The paper shows how these works are critical towards many socio-historical and biopolitical issues, such as discrimination associated with blood and blood lineages, the killing of indigenous communities, ecocide, biobanks, racial and gender-based superiority and dominance, human authority over other-than human and more-than-human beings. Such artistic practices are of great relevance for gender studies and studies of artistic research in bioculture and technoscience, where their interdisciplinary nature changes the representation and understanding of bodies in the arts and everyday culture.
Keywords: bioart; bioumetnost; body; celice HeLa; človeške celice; female contemporary artists; gender studies; HeLa cells; human cells; medical art; medicinska umetnost; posthuman feminism; posthumani feminizem; sodobne umetnice; študije spolov; telo